2011
DOI: 10.1111/j.1467-8551.2011.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

A Context‐sensitive Approach to Analysing Talk in Strategy Meetings

Abstract: The talk of managers in meetings is central to organizational life and crucial to research in strategic management, as well as managerial and organizational cognition, sensemaking and decision-making. To achieve full understanding, both the text and the context of discussion require systematic analysis, but most approaches treat context as everything that is known and observed beyond the immediate text. This obscures different readings of the text of meetings. To resolve this problem, the discourse historical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 42 publications
0
32
0
5
Order By: Relevance
“…Our analysis was inspired by a critical discursive approach that allowed us to examine these conversations and practices of interaction within their intertextual, interpersonal and socio-historical contexts (Clarke et al 2012;Fairclough 2003;Kwon et al 2009Kwon et al , 2014Reisigl and Wodak 2015;Wodak 2013), which is crucial to comprehending irony. The analysis focused on the role of language in how individuals dealt with controversy 9 as well as processes of social interaction that allowed the group to move on within meetings.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis was inspired by a critical discursive approach that allowed us to examine these conversations and practices of interaction within their intertextual, interpersonal and socio-historical contexts (Clarke et al 2012;Fairclough 2003;Kwon et al 2009Kwon et al , 2014Reisigl and Wodak 2015;Wodak 2013), which is crucial to comprehending irony. The analysis focused on the role of language in how individuals dealt with controversy 9 as well as processes of social interaction that allowed the group to move on within meetings.…”
Section: Discussionmentioning
confidence: 99%
“…A conduct-focused study of strategy making at a business division of a multinational mechanical engineering company showed that strategy workshops can be an integral part of a company's strategy process, but that opposition to and rejection of participation at the strategy workshops can constrain strategy making (Schwarz, 2009) -although the study makes recommendations for workshop planning practice, it does not analyze pre-workshop planning, it only observes the execution of strategy workshops. Similarly, a study of discursive strategies showed that "the egalitarian leadership style increases the likelihood of achieving a durable consensus" (Wodak, Kwon and Clarke, 2011, p. 593), that five discursive strategies -re/defining, equalizing, simplifying, legitimating, and reconciling -can be used to "develop shared views around strategic issues" (Kwon, Clarke and Wodak, 2014, p. 265), and that naturally occurring talk at such a meeting can be an important venue for strategizing (Clarke, Kwon and Wodak, 2012). An ethnographic study of discourse at top team meetings identified team relational dynamics as a mechanism that links emotional dynamics and strategizing processes (Liu and Maitlis, 2014).…”
Section: Zooming In On the Pre-implementation Design Phase Of Strategmentioning
confidence: 99%
“…(), to attend more to researcher reflexivity in qualitative methodologies. This growing interest in expanding the scope and diversity of management research (Cunliffe ) is reflected in recent contributions to this journal that develop diverse innovative research designs and analytical frameworks, drawing on research traditions from areas outside management (Burns et al ., ; Clarke, Kwon and Wodak ; Radaelli et al ., ). In light of this growing interest, and given the wider importance of the hermeneutic tradition within the social sciences, the relative paucity of management studies using hermeneutic‐based approaches, particularly with respect to interview‐based research, constitutes a significant oversight.…”
Section: Introductionmentioning
confidence: 99%
“…This paper responds to a highlighted need within management and organization studies to explore different approaches to qualitative research design in order to develop 'more and better tools in the qualitative domain' (Aguinis et al, 2009, p. 109), as well as responding to calls by, for example, Cunliffe (2003) and Cassell et al (2009), to attend more to researcher reflexivity in qualitative methodologies. This growing interest in expanding the scope and diversity of management research (Cunliffe 2011) is reflected in recent contributions to this journal that develop diverse innovative research designs and analytical frameworks, drawing on research traditions from areas outside management (Burns et al, 2014;Clarke, Kwon and Wodak 2012;Radaelli et al, 2014). In light of this growing interest, and given the wider importance of the hermeneutic tradition within the social sciences, the relative paucity of management studies using hermeneutic-based approaches, particularly with respect to interview-based research, constitutes a significant oversight.…”
Section: Introductionmentioning
confidence: 99%